Optimization of the Conditions for Preparation of Antirabic Diagnostic Globulins - Efimova, Marina A. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The objective of this research was to obtain highly purified antirabic immunoglobulins to diagnostically significant fractions of the rabies virus antigen obtained by buoyant density separation in a step gradient of sucrose by ultracentrifugation at 30,000 g. Materials and Methods: As an immunogen, the rabies virus antigen of the â€œOvechiyâ€ GNKI strain with infectious titer Lg 10âˆ’5.25 was used. Purification of the virus was carried out by separation in a stepwise gradient of sucrose 10â€“50% on Optima L-90K ultracentrifuge (Beckman) followed by gel filtration through the ENrichâ„¢ SEC 70 columns. Results: As a result of the separation, the fractions of the viral material, selected from the sucrose zone 10â€“20%, with the localization range of the antigenic determinants of 50â€“65 kDa were the most active, which was confirmed by the results of electrophoresis in the separating polyacrylamide gel and immunoblot. These characteristics of the obtained drug served as the basis for its use as a material for the hyperimmunization of clinically healthy sheep were carried out according to the generally accepted scheme. Hyperimmune serum with a titer of 1:6400â€“1:12800 in ELISA was used to isolate Î³-globulin fractions by three-fold reprecipitation with a saturated solution of ammonium sulfate, followed by concentration in dialysis bags, resulting in 5 final fractions of antirabic globulins. Conclusion: According to the results of ELISA and electrophoresis, globulin fractions were characterized by the greatest activity and specificity, the distribution of polypeptides in which corresponded to the location of antigenic determinants. The immunochemical properties of the obtained globulin drugs make them suitable in the future for use as specific components of improved ELISA-based express test systems for the diagnosis of rabies.